2002
DOI: 10.1002/imhj.10030
|View full text |Cite
|
Sign up to set email alerts
|

Developmental delay in young children in child welfare by initial placement type

Abstract: Estimates of developmental delay in children in out-of-home foster care range from 13-62%. Overlooked in these studies are comparisons of developmental delay differentiated by a child's initial placement type (i.e., biological parent, kinship care, or nonrelative foster care) following evaluation for possible abuse and/or neglect. The developmental status of children residing in these different placement types warrants further scrutiny by clinicians and policy makers, especially due to the recent trend towards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(49 citation statements)
references
References 35 publications
3
43
1
Order By: Relevance
“…These findings are similar to those of studies that used cognitive screening tools, but different from those that used developmental assessments. For example, Leslie, Gordon, Ganger, and Gist (2002) and Leslie et al (2005) found that rates of cognitive and motor delay and mental health concerns were not different among placement type We also found that children in foster care exhibited poorer inhibitory control than did those in kinship placements, consistent with other research that has demonstrated that children with greater socioemotional, cognitive, or health risk factors are placed in foster care at a higher rate than they are placed into kinship care (Rubin et al, 2008).…”
Section: Developmental and Health Riskssupporting
confidence: 86%
See 1 more Smart Citation
“…These findings are similar to those of studies that used cognitive screening tools, but different from those that used developmental assessments. For example, Leslie, Gordon, Ganger, and Gist (2002) and Leslie et al (2005) found that rates of cognitive and motor delay and mental health concerns were not different among placement type We also found that children in foster care exhibited poorer inhibitory control than did those in kinship placements, consistent with other research that has demonstrated that children with greater socioemotional, cognitive, or health risk factors are placed in foster care at a higher rate than they are placed into kinship care (Rubin et al, 2008).…”
Section: Developmental and Health Riskssupporting
confidence: 86%
“…Infants in this study did not receive a developmental assessment, and developmental screening tools are designed to have a high rate of false positives. The current analyses also are limited to infants under 12 months of age whereas the studies conducted by Leslie et al 2002Leslie et al , 2005 included children between birth and 3 or 5 years. Furthermore, it is possible that the biological parents of infants who experienced more serious abuse were estranged from their own family for various reasons or that their family members were not deemed appropriate to care for infants; that is, these infants may be from higher risk families and may be more difficult to care for.…”
Section: Developmental and Health Risksmentioning
confidence: 99%
“…60 Data from San Diego County suggests that only the most severely developmentally delayed or mentally ill young children are referred for assessment, whereas children with less conspicuous delays or behavioral problems are frequently missed. 38 Other studies indicate that even when recommendations for specialty medical evaluations are deemed "urgent," many children do not receive them early enough to prevent detrimental outcomes. 28…”
Section: Program Service Use For Children In Foster Carementioning
confidence: 99%
“…Research on children placed in out-of-home care suggests that between 23% and 61% of children under the age of 5 are significantly delayed when screened for developmental problems. [3][4][5][6] This elevated rate, compared with a rate of 10% to 12% of those with developmental delays in the general population, may be a result of increased risk of prenatal exposure to maternal alcohol and drug abuse, abuse and neglect in their birth homes, or increased medical conditions such as complications from low birth weight or prematurity. 7-9 Studies examining behavior problems report that as many as 25% to 40% of children under the age of 6 who enter out-of-home care have significant behavioral issues.…”
mentioning
confidence: 99%